City with a Chance : a Case History of Civil Rights Revolution. - Aukofer, Frank A. (Marquette University Press, 2007)
With unrest around the country and riots in Newark and Detroit, it became known as the long, hot summer of 1967. Milwaukee experienced a riot, too, and then became the biggest civil rights story in the nation as a white Catholic priest, along with a bunch of kids from the inner city, conducted marathon marches and demonstrations for an open housing law. It was a defining period, though not the end, of years of civil rights protests in Beertown, USA, against de facto school segregation, discrimination by a private club whose roster included members of the white power structure, and public offic.